2000
DOI: 10.1002/(sici)1097-4636(200002)49:2<238::aid-jbm12>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Metal ion release from titanium with active oxygen species generated by rat macrophagesin vitro

Abstract: The release of metal ions due to active oxygen species generated by macrophages (Mphi) phagocytosing high-density polyethylene (HDPE) particles was studied in vitro to investigate the mechanism behind the release of metal ions from titanium implants into nearby tissues in the absence of wear and fretting in vivo. To determine the effects of Mphis on metal ion release, titanium disks were immersed in different solutions and the titanium ions released from the titanium disks into each solution were quantified. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(58 citation statements)
references
References 49 publications
1
57
0
Order By: Relevance
“…This is due, partly, to the stability and corrosion resistance that results from the native titanium dioxide film that protects the metal from further oxidation [28]. It is commonly accepted that titanium exhibits high stability and corrosion resistance in vitro [29,30], although there have been reports showing the accumulation of titanium in tissues adjacent to the implant [31,32] that signifies metal release and some degree of corrosion in vivo. Aziz-Kerrzo et al [33] investigated the corrosion resistance of Ti, Ti-6Al-4V, and Ti-45Ni in a buffered saline solution using electrochemical methods.…”
Section: Surface Structure and Propertiesmentioning
confidence: 99%
“…This is due, partly, to the stability and corrosion resistance that results from the native titanium dioxide film that protects the metal from further oxidation [28]. It is commonly accepted that titanium exhibits high stability and corrosion resistance in vitro [29,30], although there have been reports showing the accumulation of titanium in tissues adjacent to the implant [31,32] that signifies metal release and some degree of corrosion in vivo. Aziz-Kerrzo et al [33] investigated the corrosion resistance of Ti, Ti-6Al-4V, and Ti-45Ni in a buffered saline solution using electrochemical methods.…”
Section: Surface Structure and Propertiesmentioning
confidence: 99%
“…Some studies using a surface reaction model have suggested that a titanium-peroxide complex is formed due to interaction with hydrogen peroxide when titanium is implanted in the human body [7][8][9] . Furthermore, the titanium surface was oxidized and dissolved by peroxide produced by bacteria and leukocytes during inflammatory reactions [10][11][12][13][14] . Similarly, in vitro studies have reported a decrease in resistance to corrosion and signs of pitting corrosion in titanium in the presence of hydrogen peroxide 6,[15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…This is due, partly, to the stability and corrosion resistance exhibited by titanium, which in turn is due to the spontaneous formation of a passive titanium dioxide "lm, typically a few nm thick, which protects the metal from further oxidation [1]. It is commonly accepted that titanium exhibits a high stability and a high corrosion resistance in vitro [2,3], although there are reports, which show the accumulation of titanium in tissues adjacent to the implant [4,5], signifying metal release and corrosion in vivo.…”
Section: Introductionmentioning
confidence: 99%